Facing Interdisciplinary Research In Syariah Researches, Findings From Applied Falak Sience - Santoso, Fattah Setiawan; Muthmainnah, Muthmainnah; Sembodo, Cipto; Subary, Subary; Al Amin, Muhammad Nur Kholis; Baheem, Nur Alfan; Baka, Paseeyah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
This working paper aims to describe the use of interdisciplinary studies in the application of Sharia, especially Islamic astronomy (Ilmu Falak). The benefit is strengthening holistic insight in applying Islamic astronomy in everyday life. This broadening of insight is assisted by the study of exact sciences which can scientifically impact the accuracy of astronomical calculations. Through a literature review, it can be found that interdisciplinary research in Sharia, especially astronomy in determining the direction of the Qibla, cannot avoid the use of science and technology that is currently developing to strengthen its fiqh norms.